Unraveling the Applicability of LbL Coatings for Drug Delivery in Dental Implant-Related Infection Treatment - Alves Pereira, Marta Maria [UNESP]; Piazza, Rodolfo [UNESP]; Santana, Amanda Paino [UNESP]; Ricardo Barão, Valentim Adelino; Malheiros, Samuel Santana; van den Beucken, Jeroen J. J. P.; de Molon, Rafael Scaf [UNESP]; de Avila, Erica Dorigatti [UNESP] (American Chemical Society (ACS), 2025)
Peri-implantitis is an inflammatory condition caused by bacterial biofilms adhered on dental implant surfaces that cause progressive tissue destruction from the host’s inflammatory response. The adverse effects of peri-implantitis progression can go beyond just losing the implant. This highlights the importance of implementing strategies to stabilize disease in the short term. Layer-by-layer (LbL) assembly is a promising avenue in the field of peri-implantitis management due to its applicability with a variety of substances, in addition to being an easy, versatile, and flexible process for multilayer formation to act directly in the affected site. In this Review, our objective is to offer comprehensive chemical and biological insights into the LbL system, clarifying its specific application as antimicrobial coatings, with concern for the physical site and purpose. Additionally, we delve deeper into the concepts of onset and progression of peri-implantitis, aiming to elucidate the precise indications for employing the LbL system as a coating for implant abutments in peri-implantitis treatment. Finally, we correlate the chemical composition of the LbL system with its functionality while also addressing the challenges posed by the uncontrolled environment of the oral cavity, which ultimately restricts its clinical applicability.
Keywords: antimicrobial coating; dental implants; drug delivery system; layer-by-layer system; peri-implantitis